Pulmonary arterial hypertension in the setting of scleroderma is different than in the setting of lupus: A review. (January 2018) - Bazan, Isabel S.; Mensah, Kofi A.; Rudkovskaia, Anastasiia A.; Adonteng-Boateng, Percy K.; Herzog, Erica L.; Buckley, Lenore; Fares, Wassim H.
Abstract: Pulmonary hypertension (PH) is a clinical syndrome that is subdivided into five groups per the World Health Organization (WHO) classification, based largely on hemodynamic and pathophysiologic criteria. WHO Group 1 PH, termed pulmonary arterial hypertension (PAH), is a clinically progressive disease that can eventually lead to right heart failure and death, and it is hemodynamically characterized by pre-capillary PH and increased pulmonary vascular resistance in the absence of elevated left ventricular filling pressures. PAH can be idiopathic, heritable, or associated with a variety of conditions. Connective tissue diseases make up the largest portion of these associated conditions, most commonly systemic sclerosis (SSc), followed by mixed connective tissue disease and systemic lupus erythematous. These etiologies (namely SSc and Lupus) have been grouped together as connective tissue disease-associated PAH, however emerging evidence suggests they differ in pathogenesis, clinical course, prognosis, and treatment response. This review highlights the differences between SSc-PAH and Lupus-PAH. After introducing the diagnosis, screening, and pathobiology of PAH, we discuss connective tissue disease-associated PAH as a group, and then explore SSc-PAH and SLE-PAH separately, comparing these 2 PAH etiologies.